(untitled) (Conference Zone, 2022)
A lot of work has been done in the public education system to form a scientific worldview among teachers, practical implementation of pedagogical knowledge, especially extracurricular work in geography lessons, and the creation of a scientifically based system, the formation of a complex based on an integrative approach to science. Thanks to these studies, feedback was received that the school improves the quality and effectiveness of students’ education.